2014
DOI: 10.1590/s1806-83242013005000025
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans biofilms and MMA surface treatment influence the adhesion of soft denture liners to PMMA resin

Abstract: The effect of Candida albicans biofilms and methyl methacrylate (MMA) pretreatment on the bond strength between soft denture liners and polymethyl methacrylate (PMMA) resin was analyzed. Specimens were prepared and randomly divided with respect to PMMA pretreatment, soft liner type (silicone-based or PMMA-based), and presence or absence of a C. albicans biofilm. Samples were composed of a soft denture liner bonded between two PMMA bars. Specimens (n = 10) were incubated to produce a C. albicans biofilm or stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
1
4
0
2
Order By: Relevance
“…Several authors corroborate the results described here for the antibacterial effect of the essential oil of Cymbopogon citrates [6], and it has been demonstrated that this substance may act as an enhancer of the antimicrobial effect of some antibiotics [27]. Interaction between Streptococcus mutans and Candida albicans has been reported in literature as increasing the adherence of the species to biofilm [28,29]. For this reason, the multispecies biofilm developed in the present study used these microorganisms as microbial association.…”
Section: Discussionsupporting
confidence: 90%
“…Several authors corroborate the results described here for the antibacterial effect of the essential oil of Cymbopogon citrates [6], and it has been demonstrated that this substance may act as an enhancer of the antimicrobial effect of some antibiotics [27]. Interaction between Streptococcus mutans and Candida albicans has been reported in literature as increasing the adherence of the species to biofilm [28,29]. For this reason, the multispecies biofilm developed in the present study used these microorganisms as microbial association.…”
Section: Discussionsupporting
confidence: 90%
“…The inadequate removal of bacteria and fungi from the denture surface can lead to further biofilm development and prolong the inflammation that may already be present in DS patients. Few in vitro models have been developed for studying the disinfection of multispecies denture biofilms, with the majority of these basing their work around the main causative agent C. albicans only (Li et al, 2010 ; Mendonca E Bertolini et al, 2014 ). Therefore, such models do not represent the complex environment observed clinically in the oral cavity and as such do not investigate the true activity of various denture-cleansing regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Poly(methyl) methacrylate (PMMA) is the main choice of denture material used clinically, however, the uneven surface results in areas of depression that provides C. albicans and other organisms the ideal surface to form biofilms and evade denture cleansing therapies (Li et al, 2010 ; Ramage et al, 2012 ; Mendonca E Bertolini et al, 2014 ). Various physical and chemical cleansing techniques both individually and in combination have been investigated with regards to denture hygiene in order to determine the optimal method for cleaning.…”
Section: Introductionmentioning
confidence: 99%
“…Одим з найбільш частих ускладнень в ортопедичній стоматології є протезні стоматити алергічного походження. При цьому контактні алергічні реакції посилюються різними факторами ендогенного і екзогенного походження, у тому числі, індивідуальною підвищеною чутливістю до пластмас [8,25,34].…”
unclassified
“…Бактеріальне обсіменіння протезів з акрилових пластмас, як показали дослідження N. Hernandez-Santos et al, спостерігається вже на 2-у добу наявності протеза в порожнині рота, до кінця 1-го тижня склад мікрофлори змінюється, і наявні вже, як мінімум, 20 видів, серед яких присутня і патогенна мікрофлора [25,33].…”
unclassified